STEAM JOBS FOR PETROLHEADSS - Rhodes, Sam , 1983- (Edge books. STEAM jobs, 2019)
Do you love watching racing cars? Then maybe you can get a job making them go faster. There are more jobs for gearheads than you probably ever realized. From classic car restorer to motorcycle designer, readers will learn about various STEM and STEAM jobs for gearheads and what it takes to get one.